Potential Mosquito Vectors for Shuni Virus, South Africa, 2014–2018 - Milehna Mara Guarido (Centers for Disease Control and Prevention, 2021)
Shuni virus is associated with neurologic and febrile illness in animals and humans. To determine potential vectors, we collected mosquitoes in South Africa and detected the virus in species of the genera Mansonia, Culex, Aedes, and Anopheles. These mosquitoes may be associated with Shuni virus outbreaks in Africa and emergence in other regions.